Pengaruh Investasi Swasta dan Pengeluaran Pemerintah Serta Konsumsi Rumah Tangga Terhadap Pertumbuhan Ekonomi Kabupaten Kutai Kartanegara - tirtawan putra perdana; Muhammad Saleh; Muhammad Awaluddin (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Tirtawan Putra Perdana, 2019, The Effect of Private Investment and Government Expenditures and Household Consumption on Economic Growth of Kutai Kartanegara (Guidance from Prof. Dr. Muhammad Saleh and Mrs. Dr. Muhammad Awaluddin).The purpose of this study was to determine the magnitude of the influence of Private Investment and Government Expenditures and Household Consumption on Economic Growth. The data from this study uses secondary data from 2010 to 2017. The analysis tool in this study used Multiple Linear Regression using SPSS version 21, Classical Assumption Test and Hypothesis Test in this study is the t test (Partial).The results of this study indicate that: 1) Private Investment has a significant and significant effect on the Economic Growth of Kutai Kartanegara. 2) Government Expenditures have a significant and significant effect on the Economic Growth of Kutai Kartanegara. 3) Household Consumption has a significant and significant effect on the Economic Growth of Kutai Kartanegara.